ذوالفقار احمد تابش کی شاعری میں مذہبی ، صوفیانہ اور معاصر مسائل: Religious, Mystical and Contemporary Issues in the poetry of Zulfiqār Ahmad Tābish (Al-Qamar, 2023)
Zulfiqār Ahmad Tābish a big name who was born in 1938 at Kamonki. He was the only son, also saw many tribulations in his early life. He was deprived of money to meet the requirements of the time for education. He wrote on of the verse in his early age, in his primary school, which according to him forget since the verse emerged in my mind. In the late 20th century, when big literary names came, one of them is Zulfiqar Ahmad Tabish, he has tried to show novelty in Urdu poetry. Zulfiqar Ahmad Tabish has written poetry keeping in mind all the rules of poetry. In Urdu poetry, along with religious poetry, he has also tried to convey current issues. In religious poetry, two of his long poems and a poem in the name of Salim-ur-Rehman are where he tried his hand at poetry, and there is also a glimpse of his prose work. In which a travelogue was published under the name of “Jawār Bhātta”. His poetry collection “Kalam Lab-e-Larzān” contains independent poems, while ”Dar-e-Neem Wā”, a collection of poetry that came out in 2019, also includes ghazals. He has expressed his deep love and devotion to religious and Sufism.
Keywords: Zulfiqār Ahmad Tābish; poetry; religious; mystical; Contemporary Issues